Perception of the accountants of the state of Mato Grosso in relation to the changes that occurred in The New Code of Civil Procedure - Kawakami, Aline; Lima, José Ricarte de; Pereira, Vanusa Batista; Costa, Enézio Mariano da; Durigon, Almir Rodrigues; Silva, Juliana Vitória Vieira Mattiello da (Seven Editora, 2024)
The New Brazilian Code of Civil Procedure (NCPC), which came into force in 2016, brought several changes, including changes related to the performance of experts. In this sense, the present study sought  to verify the perception of expert accountants in relation to the changes that occurred in the NCPC. To this end, a questionnaire with open and closed questions was prepared and sent to the respondents through personal e-mails, obtained from the website of the National Register of Expert Accountants (CNPC), using the Google Docs platform. The study was carried out with expert professionals working in the state of Mato Grosso. The evidence pointed out by the study is that 65% of the respondents are male and that  the age range of the majority of the responding experts is between 41 and 60 years old. The results also revealed that 80% of respondents are more requested to work in judicial reorganization. Regarding the perception of the accountant experts about the changes that occurred in the NCPC, the results showed that, according to the respondents, the NCPC expanded  the role of the accountant, increasing the responsibility of the expert, but emphasizing the cooperation that must exist between the parties in order to resolve disputes in a consensual manner. DOI:https://doi.org/10.56238/sevened2023.006-138